Gusaran as a Cultural Marker: Interpreting Purification, Social Recognition, and Cultural Continuity in the Gusaran Tradition of Sundanese Society: Interpreting Purification, Social Recognition, and Cultural Continuity in the Gusaran Tradition of Sundanese Society - Dadan Koswara; Luthfi Cahya Nugraha; Rangga Eka Prasetya (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2026)
The Gusaran tradition remains a living cultural practice among Sundanese communities, yet its meaning remains contested. While some studies interpret Gusaran as female circumcision, others view it as gusaran, a ritualized tooth-rubbing practice associated with girls’ life-cycle ceremonies. Previous research has primarily focused on ritual procedures, social functions, and symbolic attributes, leaving the cultural meaning of gusaran insufficiently explored. This study aims to reconstruct the cultural meaning of gusaran through an interpretive anthropological approach. Data were collected through participant observation, in-depth interviews, and document analysis, and analyzed using symbolic anthropology, ritual theory, and cultural resilience perspectives. The findings reveal that gusaran functions as a cultural marker encompassing three interconnected dimensions: purification, representing moral refinement and self-control; social recognition, legitimizing an individual’s transition within the community; and cultural continuity, facilitating the transmission of identity and collective memory across generations. The study proposes “Gusaran as a Cultural Marker” as a conceptual model explaining the persistence of Gusaran as a form of living heritage and cultural resilience in contemporary Sundanese society.